Exponents 4-2
26 represents 2⋅2⋅2⋅2⋅2⋅2 = 64
the 2 in 26 is the base
the 6 in 26 is the exponent
and together 26 it is the power!!
The base is used as a factor 6 times to produce 64
There are 3 forms here:
26 is in exponential notation
2⋅2⋅2⋅2⋅2⋅2 is in expanded notation
64 is in standard notation
You must use integer rules-- even when raising a negative number to a power!!
odd power = negative
even power = positive
(-5)3 = (-5)(-5)(-5) = -125
(-5)4 = (-5)(-5)(-5)(-5) = 625
an odd number of negative signs or an odd power---> it's negative
an even number of negative signs or an even power ---> it's positive
(-2)3 = ( -2)(-2)(-2) = -8
(-2)4 = (-2)(-2)(-2)(-2) = 16
If there is a negative BUT NO parenthesis it is ALWAYS negative
-25
is read as the opposite of 25
Look at what the exponent is touching.. and in this case it is just the 2!!
You can also think of -25 as (-1)-25
so this is -1⋅2⋅2⋅2⋅2⋅2 = -32
-24 = -2⋅2⋅2⋅2 or -1⋅2⋅2⋅2⋅2 = -16
BUT REMEMBER
(-2)4 = (-2)(-2)(-2)(-2) = +16
THis works with variables as well. WHen you substitute in for variables put the number in parenthesis!! Hugs are important in life-- and equally important in math!!
For example Solve for x
x4 - 10 when x = -2
(-2)4 - 10
+16 - 10 = 6
But what happens when the expression is
-x4 - 10? Still solve for x , when x = -2
This time
the exponent is touching just the x
-(-2)4 - 10
You must use PEMDAS and do the exponent first!!
(-2)4 = 16 so substitute that back in
-(16) - 10
becomes
-16 -10 = -26
What about 4(2y -3)2 when y = 5
substitute in
4[2(5) -3]2
4(10-3)2
4(7)2
4(49) =196
How about
-2x3 + 4y . When x = -2 and y = 3
-2(-2)3 + 4(3)
-2(-8) + 12
16 + 12 = 28
Wednesday, December 8, 2010
Subscribe to:
Post Comments (Atom)
No comments:
Post a Comment